NYPD Red 6 [compact disc, unabridged] - Patterson, James, 1947-; Karp, Marshall (Patterson, James, 1947- NYPD red mystery., 2020)
Reality star Erin Easton's wedding may have a cable crew documenting every detail. But when she disappears, her dressing room is empty but for a blood-spattered wedding gown and signs of a struggle.